2020
DOI: 10.1021/acsomega.9b04407
|View full text |Cite
|
Sign up to set email alerts
|

High-Impact Promotional Effect of Mo Impregnation on Aluminum-Rich and Alkali-Treated Hierarchical Zeolite Catalysts on Methanol Aromatization

Abstract: A systematic change of HZSM-5 (HZ5) as a catalyst of the methanol to aromatics (MTA) reaction was undertaken by employing a fixed-bed tubular-type reactor under ambient pressure, applying a weight hourly space velocity (WHSV) of 2 h–1 at 375 °C, as the first report on the application of low-Si/Al-ratio alkaline-[Mo,Na]-HZSM-5 in the MTA process. To characterize the surface and textural properties of the catalysts, powder X-ray diffraction (PXRD), nitrogen adsorption/desorption, temperature-programmed desorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 84 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…Many Mo species covering the BASs resulted in insufficient BASs to promote the polymerization and cyclization of small molecule olefins, which in turn led to an increase in the selectivity to small molecule olefins and a decrease of aromatics. 26,27 3.5.2 Effect of reaction temperature. The conversion of methanol was kept at 100% at different reaction temperatures.…”
Section: Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…Many Mo species covering the BASs resulted in insufficient BASs to promote the polymerization and cyclization of small molecule olefins, which in turn led to an increase in the selectivity to small molecule olefins and a decrease of aromatics. 26,27 3.5.2 Effect of reaction temperature. The conversion of methanol was kept at 100% at different reaction temperatures.…”
Section: Aciditymentioning
confidence: 99%
“…MoO 3 is an effective promoter in methane aromatization through activating the C-H bonds of methane molecules. 25,26 It has been reported that Mo modification promoted the oligomerization and aromatization to improve the yield of aromatics. 27 At present, there are still no reports about the modification of HZSM-5 with Zn and Mo for the coaromatization reaction coupling methanol with n-hexane.…”
Section: Introductionmentioning
confidence: 99%